Pengaruh Pengembangan Karir dan Employee Branding Terhadap Kepuasan Kerja dan Loyalitas Karyawan PT X - Siti Aminatul Fitriyah; Antin Rakhmawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study analyzes the influence of career development and employee branding on employee job satisfaction and loyalty at PT X. Given the importance of quality human resources amidst business competition and high turnover intention in Indonesia, this quantitative study examines how these factors affect employee satisfaction and loyalty. Data were collected from 94 employees of PT X through questionnaires, then analyzed using multiple linear regression and path analysis. The results show that career development and employee branding positively and significantly affect job satisfaction. Job satisfaction is also proven to significantly increase employee loyalty. Although career development does not have a direct effect on loyalty, job satisfaction fully mediates the relationship. Meanwhile, employee branding has a significant direct effect on loyalty, with job satisfaction as a partial mediator. The implications of this study emphasize the importance of career development and employee branding in HR strategies to improve employee satisfaction and loyalty, in order to support the sustainability and competitiveness of the company.